2015
DOI: 10.1186/s13104-015-1475-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and anti-microbial susceptibility pattern of group B Streptococcus among pregnant women attending antenatal clinics in Ayder Referral Hospital and Mekelle Health Center, Mekelle, Northern Ethiopia

Abstract: BackgroundVaginal colonization with group B Streptococcus (GBS) is the predominant risk factor for the development of invasive neonatal GBS diseases and puts newborns at increased risk for morbidity and mortality. This study is aimed to determine the colonization rate and antimicrobial susceptibility pattern of group B Streptococcus among pregnant women.MethodsHospital based cross-sectional study was conducted from August to December 2014 at selected health facilities. A total of 139 antenatal clinics attendee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
31
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 13 publications
12
31
9
Order By: Relevance
“…This discrepancy might be explained by the variability in the number of the studies involved in the meta-analysis, the number of pregnant women participated in between the two reviews, variations in the detection techniques (laboratory facilities) employed and biological factors among the study participants across the world. Another meta-analysis study analyzed the dataset about maternal colonization included 390 articles, 85 countries, and a total of 299, 924 pregnant women found the worldwide adjusted estimate for maternal GBS colonization was 18% (95% CI [17][18][19], with the regional variations from 11.1% (95% CI 9.9-12.4) in the Eastern Asia to 34.7% (95% CI 29.5-39.9) in the Caribbean. In the same meta-analysis study, Africa represented in the 19 studies included 36,130 pregnant women with the reported prevalence rate of 18.2% (95% and overall pooled estimate of the adjusted colonization proportion was 21.3% (95% [69] which is in consistent with our estimate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy might be explained by the variability in the number of the studies involved in the meta-analysis, the number of pregnant women participated in between the two reviews, variations in the detection techniques (laboratory facilities) employed and biological factors among the study participants across the world. Another meta-analysis study analyzed the dataset about maternal colonization included 390 articles, 85 countries, and a total of 299, 924 pregnant women found the worldwide adjusted estimate for maternal GBS colonization was 18% (95% CI [17][18][19], with the regional variations from 11.1% (95% CI 9.9-12.4) in the Eastern Asia to 34.7% (95% CI 29.5-39.9) in the Caribbean. In the same meta-analysis study, Africa represented in the 19 studies included 36,130 pregnant women with the reported prevalence rate of 18.2% (95% and overall pooled estimate of the adjusted colonization proportion was 21.3% (95% [69] which is in consistent with our estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Primary studies conducted in the East African countries showed the colonization rates ranged from 3.0% to 28.8% [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]; Central Africa,20.0% [27,28]; Western Africa, 2.5% to 34.2% [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]; Southern Africa, 1.77% to 48.23% [49][50][51][52][53][54][55][56][57]…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, few studies have been conducted on GBS [11, 12, 15–17] although infant mortality is high in this population. Until today, there are no public health policies or strategies in Ethiopia aimed at the reduction of GBS neonatal infection.…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus agalactiae (S. agalactiae) is a gram-positive bacterium which belongs to the Lance eld Group B streptococcus (GBS). It is part of the normal ora of the gastrointestinal and female genitourinary tracts, and it is present in the genital tract of about 20-60% of pregnant women 1 . Nearly 20-40% of healthy women are colonised by GBS, and 50-70% of infants born to these mothers become infected with it 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Mortality of GBS in neonates is over 50% and is particularly high in preterm infants 3 . Vaginal colonisation by GBS during pregnancy is associated with premature delivery and still births 1 .…”
Section: Introductionmentioning
confidence: 99%